On new emerging concepts of Tarakan Sedimentary Basin – a Petroleum Digital Ecosystem (PDE) - Nimmagadda, Shastri; Dreher, Heinz; Noventianto, Andy; Mustafa, A.; Fiume, G. (2012)
Petroleum system and its elements are often narrated for each and every oil and gas field in each and every petroleum-bearing sedimentary basin. Petroleum-bearing sedimentary basin is an emerging digital ecosystem within the generic petroleum system. On the broader scale, total petroleum system (where geology has no boundaries) can usefully be perceived as a digital petroleum ecosystem. Significance of this concept is to make connectivity among both onshore and offshore petroleum subsystems, for ex-ample, Tarakan Basin (an Indonesian Onshore-Offshore basin, a transition zone with more than 50,000sq km areal extent), through attributes of their elements, processes and modeling them by contextualization and specifications. Unless the phenomenon on integration of elements and processes among petroleum systems of sub-basins is under-stood, petroleum system existence (both at “field” and “basin” scales) and its potentiality, including the phenomenon of “inter-connectivity” among ecosystems, cannot be well explained. Specification of digital representation, visualization, and interpretation are other value added methods. Values cannot be added to petroleum accumulations and volumes, unless these processes are explicitly explained. Authors propose an ontology based data warehousing and mining technology, in which, conceptualization and contextualization of multiple data dimensions’ are modelled within Tarakan basin (for example, elements and processes of pe-troleum system), besides their integration (within a data warehouse environment) and data mining of interpretable emerging petroleum digital ecosystems. Multidimensional data warehousing and mining models facilitate an effective interpretation of petroleum systems, minimizing the ambiguities involved during knowledge mapping of structure and reservoir qualities, not only for exploration and field development plans, but for reserve computations.